1995
DOI: 10.3109/02699059509008185
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive moderators of outcome following traumatic brain injury: A conceptual model and implications for rehabilitation

Abstract: This paper presents a conceptual model describing the relationships between quality of life outcomes following traumatic brain injury (TBI), coping patterns, and beliefs regarding self-efficacy to assist health-care professionals in understanding the complexity of social and psychological sequelae of TBI. The mode hypothesizes that long-lasting cognitive, behavioural, emotional psychiatric, and interpersonal after-effects of TBI may create a real life 'learned helplessness' with consequent deficits in coping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 52 publications
2
75
0
Order By: Relevance
“…The coping style is influenced by the appraisal of a stressful situation, and it affects psychosocial outcomes either negatively or positively [8]. Infrequent use of passive coping strategies and high use of reframing and seeking spiritual support have been associated with better adjustment outcomes in caregivers of patients with acquired brain injury, such as stress reduction and a high quality of life [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The coping style is influenced by the appraisal of a stressful situation, and it affects psychosocial outcomes either negatively or positively [8]. Infrequent use of passive coping strategies and high use of reframing and seeking spiritual support have been associated with better adjustment outcomes in caregivers of patients with acquired brain injury, such as stress reduction and a high quality of life [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancy scores can range from 268 to 68. Higher discrepancy scores are associated with more severe SA deficits, while negative scores are rare and might show a patient's overestimation of his impairment (Cicerone, 1991;Prigatano & Altman, 1990), possibly due to a high level of emotional distress (Fleming et al, 1998;Godfrey et al, 1993) or to the development of self-limiting belief systems in which TBI patients overrate the effects of their injury in everyday life (Moore & Stambrook, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ABI, selfreport data may be adversely affected by cognitive difficulties (Port, Willmott & Charlton, 2008). Nevertheless, the use of Likert scales comprising relatively short and concrete items has been shown to yield accurate data in such populations (Moore et al, 1995). This seemed to be the case in the current study as all measures demonstrated good internal consistency reliability (Cronbach, 1951).…”
Section: Limitationsmentioning
confidence: 50%
“…Accordingly, findings supported theoretical assumptions that self-efficacy may be derived through causal attributions (Schwarzer & Renner, 2000). For example, Moore et al (1995) proposed an overlap between control and self-efficacy beliefs following TBI, such that "generalized expectancies [...] arising from pervasive non-contingent and suboptimal outcomes in many aspects of the TBI patient's life, lead to feelings of low personal control over the environment and contribute to lowered self-efficacy" (p. 118).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation